Antibacterial activity on stem and leaf of neptunia natans extract / Nur Nazihani Muhamad Nazir - Muhamad Nazir, Nur Nazihani (2018)
The leaf and stem of methanolic extraction of Neptunia natans were investigated for their antibacterial activity against Salmonella spp. (Gram negative bacteria) and Staphylococcus spp. (Gram positive bacteria). The tests were conducted in vitro and two different methods, which were disc diffusion and agar well diffusion method, were used to evaluate this study. Both of the methods have almost similar technique but it differs in term of sensitivity towards the metabolites compound in the plant. Three different dose of concentration were used to measure the antibacterial activity against selected bacteria which were 500mg/ml, 700mg/ml and 1000mg/ml. The inhibition zones for both samples of leaf and stem of Neptunia natans were measured and compared. Streptomycin and dimethyl sulfoxide (DMSO) act as positive and negative control respectively. Leaves extract from methanol demonstrate a relatively higher inhibition zones of compared to stem. Leaves exhibit 15.07±2.30mm zone of inhibition against Staphylococcus spp. using agar well diffusion method meanwhile, stem showed 11.50±1.06mm zones of inhibition against the same bacteria by using the same method. However, the value of significance difference in statistical analysis were all p>0.05. This indicate that the result showed no significance difference between all the three different concentrations of the extracts used. The minimum inhibitory concentration (MIC) for leaves against both of the bacteria was 62.5mg/ml. Concurrently, 125mg/ml were regarded as MIC for stem methanolic extract. Thus, it can be concluded that the leaves have a better potential to become an antibacterial agent compared to the stem.